Study of Gafchromic EBT film response over a large dose range - Martišíková, Mária; Jäkel, Oliver (Physics in medicine and biology, 2010)
Presently Gafchromic EBT films are widely used for relative dose verification in standard radiation therapy using high-energy photons, inclusive IMRT. The use of films for dosimetry in medical ion beams is more complicated due to the strongly inhomogeneous dose deposition by ions on microscopic level. Track structure models, presently used to describe dosimeter response as a function of the ion field properties, are based on input information which can be obtained from the film response in photon beams. We therefore studied the performance of Gafchromic EBT films, ancestors of currently available EBT2 films, in 60Co photon beams.